Ecosystem Models and Effort Simulations of an Untrawled Gulf in the Central Aegean Sea - Dimarchopoulou, Donna; Keramidas, Ioannis; Tsagarakis, Konstantinos; Tsikliras, Athanassios C. (Frontiers in Marine Science, 2019)
Ecosystem models can be used as fisheries management tools in the context of a holistic approach and view of assessing the status of aquatic ecosystems and proposing plans of action. The Ecopath with Ecosim modelling suite has been widely used to describe exploited marine systems and perform simulations over time. Pagasitikos Gulf is a shallow semi-enclosed gulf in the western coast of the central Aegean Sea that is characterized as semi-protected, with a bottom trawling ban in force since 1966. In this study, an Ecopath model was constructed including 31 functional groups of organisms of lower to higher trophic levels, while Ecosim temporal simulations were run for 18 years (2008-2025), including the calibration period (2008-2017). An overall decrease in biomass and catch of the studied marine resources was observed by the end of the simulation period, due to fisheries exploitation as well as environmental factors. To examine the effect of fishing, three different scenarios were investigated, all aiming towards fishing effort reduction by 10, 30 and 50% compared to the initial business-as-usual scenario, applied to both fleets operating in the area (purse seiners and small-scale). All examined scenarios led to higher total biomass compared to the basic Ecosim simulation (the higher the reduction in fishing effort, the higher the increase in biomass), while catches were significantly lower in all cases as a result of less fishing. The most profound biomass increase with reduced fishing effort was observed in other larger pelagics, anchovy, anglerfish, sharks and rays, mackerels, hake and other gadiforms. In conclusion, reducing the exploitation levels of the ecosystem is a key factor that contributes to rebuilding of marine resources.